SUBSTANTIATING OPTIMUM PARAMETERS AND EFFICIENCY OF ROTARY BRUSH CUTTERS - Bukhtoyarov, Leonid; Kunickaya, Olga; Urazova, Alina; Perfiliev, Pavel; Druzyanova, Varvara; Egipko, Sergey; Burgonutdinov, Albert; Tikhonov, Evgeniy (Journal of Applied Engineering Science, 2022)
The problem of untimely forest thinning is quite common in today’s society. It leads to the emergence of the underbrush, which negatively impacts the growth and development of young trees. Therefore, this work aims to estimate the feasibility of applying a new rotary brush cutter model to eliminate excessive vegetation. The dependence of the tractor’s speed when removing underbrush with different diameters of tree trunks was established by performing mathematical modeling to optimize the brush cutter parameters. Three types of flexible inertia cutting devices were investigated: flat knives, sprocket chains, and knife chains. Knife chains are the most optimal choice as they cut plants most efficiently (94.61% and 92.5% for two-year and three-year underbrush, respectively). They also show the lowest energy consumption for underbrush with a trunk between 1 and 2.4 cm in diameter. Further experiments are required to determine if the developed mathematical model can be used for more neglected forestry stands.